Enhanced management strategy of synchronous percutaneous biopsy and microwave ablation in patients with lung ground-glass opacities undergoing antithrombotic treatment: a clinical perspective on our experience - Wang, Nan; Chen, Guoqiang; Jin, Bingjie; Lu, Wenjing; Xu, Jie; Xu, Jingwen; Xue, Guoliang; Ye, Xin (Frontiers in Oncology, 2025)
ObjectiveThis retrospective study was conducted to delineate our experience in managing perioperative antithrombotic agents in patients receiving antithrombotic therapy underwent percutaneous biopsy and microwave ablation (B+MWA) for lung ground-glass opacities (GGOs).MethodsThe study comprised 67 patients with GGOs who receiving antithrombotic therapy underwent B+MWA sessions from January 1, 2020, to May 31, 2022. During the perioperative period, patients who received rivaroxaban as a bridging drug were assigned to Group A, and who interrupted the antithrombotic therapy were assigned to Group B. Information about the technical success rate, positive biopsy rate, local control rates, and major bleeding and thrombotic complications were collected and analyzed.ResultsGroup A comprised 36 patients (19 males; mean age, 67.97 ± 8.49 years), while Group B comprised 31 patients (12 males; mean age, 65.48 ± 4.32 years). The technical success rate was 100%. The positive biopsy rates were 94.44% and 96.77%, respectively. In group A and B, the overall local control rates at 6, 18, and 24 months were 100.0% vs. 100.0%, 94.44% (34/36) vs. 96.77% (30/31), and 86.11% (31/36) vs. 87.10% (27/31), with no significant difference between the two groups (p = 0.2156). During the perioperative period, a single case of lower extremity venous thrombosis was identified in Group A, while three cases of lower extremity venous thrombosis, one case of new-onset cerebral infarction, and one case of new-onset pulmonary embolism were identified in Group B, with no statistically significant difference in the overall incidence of bleeding and thrombotic complications between the two groups.ConclusionsCompared with direct interruption of antithrombotic therapy, the use of rivaroxaban in the perioperative period of B+MWA in patients with GGOs who are receiving antithrombotic therapy can reduce the incidence of severe thrombotic complications without increasing the risk of bleeding, with a satisfactory effectiveness.